The experience of engaging in occupation following stroke: a qualitative meta-synthesis - Williams, Shoshannah; Murray, Carolyn (© 2013 British Journal of Occupational Therapy, 2017)
This review was published in the British Journal of Occupational Therapy [© 2013 The College of Occupational Therapists Ltd.] and The Journal's website is at: https://goo.gl/LGmjo7